Legal Protection For Users of Illegal Online Loan Services Regarding Personal Data Confidentiality - Nugroho, Fajar Seto; Ningtias, Ayu Dian; Bagaskara, M. Reza Satya (Universitas Islam Lamongan, 2024)
ABSTRACT This research is based on the fact that globalization has driven the development of information and communication technology, which in turn has changed people's lifestyles and various aspects of life, including the economy. The transition from a traditional manufacturing-based economy to a digital economy based on information technology and creativity is known as the creative economy. However, information technology also brings challenges, such as data security issues in online loans. Fintech (financial technology) has become a significant innovation in the financial sector, facilitating financial transactions through services such as e-commerce and online loans. The method in this research is to use the Normative legal research method using a legislative approach and a conceptual approach. The legal materials in this study are primary legal materials and secondary legal materials. From the results of the study, it can be concluded that: The government has made efforts to provide legal protection against possible crimes that occur to consumers of illegal online loans through preventive and repressive actions. Preventive actions are carried out through the Electronic Information and Transactions Law (ITE), Law Number 27 of 2022, concerning Personal Data Protection (PDP Law), and the role of the Financial Services Authority (OJK) in supervising the circulation of online loan services. Repressive legal protection is implemented through Article 2 Paragraph 1 and Article 15 Paragraph 2 of the PDP Law, Law Number 11 of 2008 Article 26 Paragraph 1 concerning the ITE Law, and other laws that stipulate sanctions such as fines, imprisonment, and other additional penalties. Law enforcement against perpetrators of personal data abuse in the context of illegal online loans includes two main approaches, judicial and non-judicial legal efforts. Judicial legal efforts involve the court process to resolve disputes after violations and unlawful acts occur based on the PDP Law, the ITE Law, and Article 368 of the Criminal Code. Meanwhile, non-judicial legal efforts involve complaints to relevant institutions, such as the OJK, Kominfo, and the Police, which have a role in supervising, imposing administrative sanctions, and conducting investigations into these violations. This approach emphasizes the importance of cooperation between various institutions to ensure effective law enforcement against illegal practices in the online lending sector.